2017
DOI: 10.1130/b31659.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential compaction over Late Miocene submarine channels in SE Brazil: Implications for trap formation

Abstract: We used high-quality three-dimensional (3-D) seismic data to quantify the timing and magnitude of differential compaction over a Late Miocene submarine channel complex in SE Brazil (Espírito Santo Basin). A thicknessrelief method was applied to quantify the thickness variations in strata deposited over the channel complex. We found that differential compaction started after the channel complex was buried by ~200 m of strata, as revealed by thinning horizons observed over a compaction-related anticline. The siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Schmiedel et al. (2017) also showed that the dome above the Tulipan sill was formed by a combination of syn‐sill‐emplacement forced folding and post‐emplacement differential compaction, the latter of which is an important mechanism for forming subtle traps for hydrocarbons (Ward, Alves, & Blenkinsop, 2018). This work also shows that hydrothermal vent complexes play an important role in controlling the plumbing system of a volcanic sedimentary basin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmiedel et al. (2017) also showed that the dome above the Tulipan sill was formed by a combination of syn‐sill‐emplacement forced folding and post‐emplacement differential compaction, the latter of which is an important mechanism for forming subtle traps for hydrocarbons (Ward, Alves, & Blenkinsop, 2018). This work also shows that hydrothermal vent complexes play an important role in controlling the plumbing system of a volcanic sedimentary basin.…”
Section: Discussionmentioning
confidence: 99%
“…If forced folds are created above saucer-shaped sills, this creates a possible trapping mechanism as evidenced by the Tulipan well in the outer Møre Basin, where a small gas discovery was recorded in a dome above a saucer-shaped sill (Holford et al, 2012;Kjoberg et al, 2017;Polteau et al, 2008;Schmiedel et al, 2017). Schmiedel et al (2017) also showed that the dome above the Tulipan sill was formed by a combination of syn-sill-emplacement forced folding and post-emplacement differential compaction, the latter of which is an important mechanism for forming subtle traps for hydrocarbons (Ward, Alves, & Blenkinsop, 2018). This work also shows that hydrothermal vent complexes play an important role in controlling the plumbing system of a volcanic sedimentary basin.…”
Section: Implications Of Reutilising Magmatic Migration Pathways Inmentioning
confidence: 97%
“…In addition, pre‐existing sedimentary features may have an expression on the sea‐floor, such as differential compaction of stacked channels (e.g. Ward, Alves, & Blenkinsop, 2017) and mass transport deposits (e.g. Ortiz‐Karpf, Hodgson, & Mccaffrey, 2015; Zhao, Qi, Patacci, Tan, & Xie, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in the decay stage, subtle structural highs control major avulsion nodes along or immediately down-dip of fold flanks due to occasional re-activation of salt movement through squeezing (Figure 18c). Differential compaction of thicker minibasin fill (>200 m burial sensu Ward et al, 2017) may also play an important role in controlling avulsion node localities through creating gradual gradients. Although most of the salt-cored structures are low-relief during this stage, some large structures may be long-lived and continue blocking sediment transport pathways and ponding sediments ( Figure 18c).…”
mentioning
confidence: 99%
“…Domes caused by differential compaction of the local heterogeneous stratigraphy (e.g. Ward, Alves, & Blenkinsop, 2018). Elongated domes created by crystalline basement rock uplifted along faults that parallel the long axis of the dome structures (e.g.…”
Section: Discussionmentioning
confidence: 99%